Current status of virtual reality simulation education for orthopedic residents: the need for a change in focus - Cate, Graham; Barnes, Jack; Cherney, Steven; Stambough, Jeffrey; Bumpass, David; Barnes, C. Lowry; Dickinson, Karen J. (Global surgical education : journal of the Association for Surgical Education, 2023)
Introduction Advances in technology are changing surgical education. Simulation provides an important adjunct to operative experience. This pedagogy has arguably become more important in light of the COVID-19 pandemic, with resultant reduction in operative exposure for trainees. Virtual reality (VR) simulators may provide significant contribution to experiential learning; however, much of the investigative focus to date has, correctly, been on establishing validity evidence for these constructs. The aim of this work was to perform a scoping review to assess the current status of VR simulation education to determine curricular development efforts for orthopedic residents. Methods With a trained medical librarian, searches of PubMed, EMBASE, and Web of Science were conducted for all articles in the last 10 years (September 2011–September 2021). Controlled vocabulary Medical Subject Headings (MeSH) terms and natural language developed with subject matter experts describing virtual reality or VR simulation and orthopedic training were used. Two trained reviewers evaluated all abstracts for inclusion. Exclusion criteria were all articles that did not assess VR simulation education involving orthopedic residents. Data were extracted from the included full-text articles including: study design, type of participants, type of VR simulation, simulated orthopedic skill, type of educational event, learner assessment including Kirkpatrick’s level, assessment of quality using the Medical Education Research Study Quality Instrument (MERSQI), and level of effectiveness (LoE). Results Initial search identified 1,394 articles, of which 61 were included in the final qualitative synthesis. The majority (54%) were published in 2019– 2021, 49% in Europe. The commonest VR simulator was ArthroS (23%) and the commonest simulated skill was knee arthroscopy (33%). The majority of studies (70%) focused on simulator validation. Twenty-three studies described an educational module or curriculum, and of the 21 (34%) educational modules, 43% were one-off events. Most modules (18/21, 86%) assessed learners at Kirkpatrick level 2. With regard to methodological quality, 44% of studies had MERSQI 11.5–15 and 89% of studies had LoE of 2. Two studies had LoE of 3. Conclusion Current literature pertaining to VR training for orthopedic residents is focused on establishing validity and rarely forms part of a curriculum. Where the focus is education, the majority are discrete educational modules and do not teach a comprehensive amalgam of orthopedic skills. This suggests focus is needed to embed VR simulation training within formal curricula efforts guided by the work of Kern, and assess the efficacy of these against patient outcomes.